Cordially - The untouchable. An approach on ’Le toucher, Jean-Luc Nancy’ - Caneda Lowry, Santiago (Escritura e Imagen, 2019)
The untouchable, a chance of touching the untouchable and the respect of this law of touch itself, these are some of the key themes of Jacques Derrida’s Le toucher, Jean-Luc Nancy. This paper presents a critical reading of this issues with the aim of easing and clearing the path to Derrida’s patient and rigorous work on Jean-Luc Nancy. This law of touch goes beyond the discussion on perception and gets on the track of an ethics involved in the very definition of this sense. A touch that no longer refers exclusively on the sense, but on the cordiality and respect of the contact with the other. On this road to the core of what Nancy claims to be the untouchable, we’ll also review the caress in the work of Lévinas, as it’s one of the best examples of the risks involved when trying to touch beyond touch itself. Once this path is cleared, we’ll approach the works of Nancy on the body and its deconstruction, as also the great deal that he sees in a posthumous note of Freud. Finally, this paper looks for a clearer but solid access to the oeuvre of Jean-Luc Nancy, and its cleverness in face of the preceding phenomenological highlights.